Experiências de mediação com artefatos didáticos no contexto da educação a distância da Universidade Federal de Goiás no curso de especialização África em Arte-Educação: construção de objetos pedagógicos - Gualtieri, Nicolas Andres (2017)
The following paper aims the relationship between students, their daily ex-periences at África em Arte-Educação: Construção de Objetos Pedagógicos, a distance learning graduate course and audiovisual didactic artifacts, made by the CIAR-UFG (Centro Integrado de Aprendizagem em Rede). Five stu-dent stories were collected from this course, in order to get a critical evalua-tion and collecting feedbacks that will help improve the student-professor relationship, and especially the creation of audiovisual didactic content for distance learning courses at Universidade Federal de Goiás.